Finite element simulations of auxetic structure combined with honeycomb using unidirectional continuous carbon fiber composite properties - Nathália Mello Mascarenhas Paixão; Antônio Ferreira Ávila (The Journal of Engineering and Exact Sciences)
Metamaterials have been studied over the last few decades, as they may exhibit peculiar mechanical behavior. An example is the re-entrant auxetic structure, which can display negative Poisson ratio. Likewise, the honeycomb structure has also been widely used, mainly in sandwich-panels. Despite several studies including these geometries, the use of composite as raw material has not been reported in the literature, so this work aimed to perform finite element simulations of combined honeycomb and re-entrant auxetic structures using properties of continuous, unidirectional carbon fiber composite in epoxy matrix. For this, three types of modeling were used: beam, shell and solid and two sets of constraints were applied for each model. By analyzing the total deformation profiles obtained for these three models, it was possible to observe that both beam and shell modeling results were close to the three-dimensional modeling when applying a vertical compression displacement, in which beam modeling showed a better approximation. On the other hand, when applying the compression displacement horizontally, the beam modeling proved to be inadequate, while the shell modeling presented values close to the solid modeling. Therefore, it is concluded that it is possible to model similar structures using shell element instead of solid element.